PERSONALITY TRAITS AND LOW CREATIVITY ARE KEY FACTORS IN VICTIMS OF MOBBING - Conte, Stella (International Journal of Psychosocial Rehabilitation, 2020)
Mobbing is an escalating process during which the person becomes the target of negative social acts. It is associated with psychological problems such as: anxiety, depression and loss of self- esteem. Some researches on mobbing described victims as conscientious, rigid and compulsive, with pre-existing symptoms of anxiety and depression.The personality of victims could play a critical role in bullying, hence some characteristic within individuals may predispose victims to being bullied. Furthermore, victims of mobbing were described as having lower social skills. Thus, the victims of mobbing may exhibit rigid answers to the attacks thereby reinforcing the mobber. These answers can be interpreted aa a lack of creativity.In this context, the current study investigates personality, according to the Big Five theory, and creativity. This study was carried out on 58 subjects divided into: victims with 30 subjects and controls with 28 subjects. Both groups were homogeneous for age and jobs. Results showed that victims exhibit: lower creativity, lower energy, lower emotional stability, lower openness and lower creativity (fluency, flexibility and originality) when compared to controls. Hence, personality and creativity seem to be problematic in victims of mobbing and play an important role in mobbing behavior.